1998
DOI: 10.1007/pl00007619
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin is Increased in Epithelial Lining Fluid in Fibrotic Lung Disorders

Abstract: Tenascin is an extracellular matrix glycoprotein increased immunohistochemically in tumorous and fibrotic lung tissues as demonstrated by immunohistochemistry. We hypothesized that in bronchoalveolar lavage (BAL) fluid also the tenascin concentration would be elevated in patients with various fibrotic lung disorders. The aim of our study was to investigate whether BAL fluid tenascin would be increased compared with serum tenascin in patients with usual interstitial pneumonia (UIP), sarcoidosis, and extrinsic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…We also show a significant increase in circulating TN-C levels in SSc patients following the onset of PF compared to the same patients prior to the development of PF. Our findings, in concert with those reported by Histomi et al and Kaarteenaho-Wiik et al , suggest that elevated serum TN-C levels can serve as markers of lung fibrosis in SSc and related diseases (20, 32). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also show a significant increase in circulating TN-C levels in SSc patients following the onset of PF compared to the same patients prior to the development of PF. Our findings, in concert with those reported by Histomi et al and Kaarteenaho-Wiik et al , suggest that elevated serum TN-C levels can serve as markers of lung fibrosis in SSc and related diseases (20, 32). …”
Section: Discussionsupporting
confidence: 90%
“…In that context, not only is IGFBP-3 known to modulate the activity of several MMPs, but it may also regulate levels and/or activity of tissue inhibitors of MMP (TIMP), thus altering the balance of MMP/TIMP and thus reducing the degradation of matrix proteins such as TN-C that can then contribute to aberrant tissue repair and fibrosis. In fact, evaluation of epithelial lining fluids from patients diagnosed with UIP, sarcoidosis, and allergic bronchiole-alveolitis (hypersensitivity pneumonitis) demonstrated elevated levels of TN-C compared to those of healthy controls (20). Also, immunoreactivity studies of bronchial biopsies have shown higher levels of TN-C in the sub-epithelial basement membranes of patients with chronic asthma as opposed to healthy controls (21).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress response proteins are increased in the fi brotic lung tissue of individuals with SFTPC mutations consistent with aberrant stress response as a component of disease. [26][27][28] Expression of a common human SFTPC mutation specifi cally in the lungs of mice resulted in severe disruption of lung development. 29 This fi nding is consistent with the deleterious effects of the mutated pro-SP-C in human lung disease wherein the adaptive mechanisms to cope with a cytotoxic or misfolded pro-SP-C are overwhelmed.…”
Section: Pathogenesis Of Interstitial Lung Disease In Children and Admentioning
confidence: 99%
“…Several of the transcripts in this cluster have emerging roles in pulmonary fibrosis, including tissue inhibitor of metalloproteinase 1 (TIMP1), tenascin C (TNC), secreted phosphoprotein 1 (SPP1), and frizzled homolog 1 (Drosophila) (FZD1) (26,27) (Figure E3). Other increased transcripts included: serine (or cysteine) peptidase inhibitor, clade F, member 1 (SERPINF1), and lumican (LUM).…”
Section: Cluster IIImentioning
confidence: 99%